2013
DOI: 10.1371/journal.pone.0059902
|View full text |Cite
|
Sign up to set email alerts
|

Altered Default Network Resting-State Functional Connectivity in Adolescents with Internet Gaming Addiction

Abstract: PurposeExcessive use of the Internet has been linked to a variety of negative psychosocial consequences. This study used resting-state functional magnetic resonance imaging (fMRI) to investigate whether functional connectivity is altered in adolescents with Internet gaming addiction (IGA).MethodsSeventeen adolescents with IGA and 24 normal control adolescents underwent a 7.3 minute resting-state fMRI scan. Posterior cingulate cortex (PCC) connectivity was determined in all subjects by investigating synchronize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
110
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(125 citation statements)
references
References 82 publications
9
110
1
5
Order By: Relevance
“…Enhanced visual motor coordination and impaired visual and auditory function had been suggested in IGD based on the result of ReHo [10] . Further, altered default network resting-state FC to the posterior cingulate has been found in 17 adolescents with IGD [12] . These results demonstrate inconsistent results of FC in IGD.…”
Section: The Functional Connectivity Of Igdmentioning
confidence: 97%
“…Enhanced visual motor coordination and impaired visual and auditory function had been suggested in IGD based on the result of ReHo [10] . Further, altered default network resting-state FC to the posterior cingulate has been found in 17 adolescents with IGD [12] . These results demonstrate inconsistent results of FC in IGD.…”
Section: The Functional Connectivity Of Igdmentioning
confidence: 97%
“…In a relatively small resting state fMRI study, internet addiction was associated with reduced functional connectivity versus controls across distributed neural circuitry, particularly implicating the bilateral dorsal striatum (putamen), and connections between cortical and subcortical regions (Hong et al 2013). Another resting state fMRI study, this time in a larger sample of adolescents with internet gaming addiction versus controls, found increased functional connectivity in the bilateral cerebellum and middle temporal gyrus; and reduced connectivity involving the bilateral inferior parietal lobule and right inferior temporal gyrus (Ding et al 2013).…”
Section: Neurobiology Of Internet Addictionmentioning
confidence: 99%
“…Most of the impaired connections involved the subcortical brain region. Ding et al [55] reported that subjects with IGD exhibited increased FC in the bilateral cerebellum, posterior lobe, and middle temporal gyrus but decreased FC in the bilateral inferior parietal lobe and right inferior temporal gyrus. Three studies reported increased FC or ReHo over the cerebellum.…”
Section: Resting-state Fmri Studymentioning
confidence: 99%